Cognition of emergency contraception: an assessment among WRA in a rural community of West Bengal - Dasgupta, Aparajita; Roychoudhury, Nivedita; Pal, Dipak; Bandyopadhyay, Lina; Suman, Sweta; Mohanta, Munu (International Journal Of Community Medicine And Public Health, 2019)
Background: Emergency Contraception (EC) is an important option for women exposed to unprotected sex to prevent unintended pregnancy and induced abortion. EC has a potential to offer women an important option for fertility control. The objective of the study was to assess knowledge about Emergency Contraception among currently married women of reproductive age in a rural area of West Bengal. Methods: A community based cross sectional study was conducted on 608 currently married women of reproductive age for 1 year from May 2017 to April 2018. Questionnaire was administered to women on knowledge of emergency contraception (EC). Data was analyzed in SPSS version 16. Results: Among the study participants 66% had knowledge of emergency contraception. A small number (8.9%) of the total participants ever used EC to prevent pregnancy. Only 65.3% of them had correct knowledge regarding timing of EC. Effectiveness of post-coital pill was known to them while none of these women were aware of the existence of Intra Uterine Contraceptive Device (IUCD) insertion as an option for EC. Conclusions: Marked lacunae were observed regarding knowledge and practice of emergency contraceptives among the WRA. Proper and correct knowledge on Emergency Contraception is of urgent need among all sexually active women especially in this country for population stabilization.